The Effect of Edutainment Learning Model on Student Learning Outcomes in Islamic Education Learning at SMP Muhammadiyah 04 Medan - Dwi Purnamaningsih (Indonesian Journal of Education and Mathematical Science, 2022)
Edutainment is a learning model that is designed to blend entertainment and educational content in harmony so that the activities that occur in the classroom are fun. This study aims to determine the effect of implementing the edutainment method in learning Islamic education on student learning outcomes at SMP Muhammadiyah 04 Medan.The research method used was a quasi-experimental method (pseudo). The population used in this study was class VIII students, totalling 80 people. The sample in this study were students of class VIII-A, totalling 33 students as the experimental class and students of class VIII-B as the control class. To obtain data on the implementation of the edutainment method, the researcher used a questionnaire technique, while to get data related to student learning outcomes in Islamic education subjects, they used a questionnaire and pretest/posttest.Meanwhile, to obtain other supporting data used interview techniques and documentation. Based on the results of the research data analysis using the t-test with a significance level of 5%, a value of 5% was obtained. If t count t table then h0 is rejected and Ha is accepted, which was 3.879 2.04. It means that there is a difference in learning outcomes between using the edutainment method and the conventional method so it can be concluded that the edutainment method influences student learning outcomes in class VIII PAI learning at SMP Muhammadiyah 4 Medan.